The Effect of Internal Control System on Village Fund Management Accountability; Empirical Study in Kudus Regency - Afifi, Zaenal; Mulyanto, Mulyanto; Nugroho, Dennyca Hendriyanto (Jurnal Magister Administrasi Publik, 2021)
internal control is a process influenced by human resources and information technology systems designed to help organizations achieve a goal. Process accountability in managing village funds is the willingness of village fund managers to accept responsibility for what is assigned to them efficiently, effectively, fairly, and transparently by involving the community. The demand for accountability on public institutions, both at the central and regional levels, has become a phenomenon of the development of the public sector, especially in the government sector. The purpose of this study was to analyze the effect of the internal control system on the accountability of village fund management. The population in this study were village officials in all villages in Kudus Regency. The number of village officials in all villages in the Kudus Regency is 492, while the sample obtained is 83 respondents. The research method used is quantitative research with primary data types. The data collection technique in this study was by distributing questionnaires to each village apparatus. Determination of the selected respondents using the Convenience Sampling technique. The test method uses a Structural Equation Models (SEM) approach, using the alternative method WarpPLS 7.0. The results showed that the internal control system had a significant positive effect on the accountability of village fund management.